Analisis Karakter Menggunakan Teori Filsafat Pendidikan Pada Anak Panti Asuhan Sahabat Keluarga Indonesia - Sani Susanti; Khalida Rahmah; Nazwa Mutia Syafitri; Diva Novita Angely Putri Purba (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Based on the results of research conducted by researchers at the Indonesian Family Friends Orphanage in Medan, located at Jalan Haji Hospital Ujung Medan, which was conducted during two meetings which raised the subject of the character of each child at the Indonesian Family Friends Orphanage. The character of the Children from the Indonesian Family Friends Orphanage is a problem that needs to be studied in order to find the right solution in shaping the character of these children. In this research, quantitative methods were used. The subjects in this research were children from an orphanage with levels ranging from early childhood to junior high school students with a total of 10 children in the orphanage, 7 girls and 3 boys. The data analysis used to overcome the problems presented in this research is descriptive analysis. Descriptive analysis aims to describe the character of the children in the orphanage. In carrying out observations, we find out what problems exist among children in orphanages and what factors cause a child to become the way he is.